(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The Internet is a huge network that connects people worldwide. Internet use among youths in the contemporary world is seen as a major part of their life because of its progressive features. People utilize the internet for entertainment, social interaction, and many other online activities. Therefore, people use the internet for multiple purposes and are obsessed with it. Excessive use of the internet affects the mental state and emotions of many young people. Various studies have focused on the association between internet overuse and unstable emotions. Numerous studies have shown that internet addiction is on the rise in many nations, including Italy, Germany, China, & United States and that it is at an alarming level in several countries. Many studies have also investigated that excessive internet use can lead to an inability to express one's feelings and an inability to understand the feelings of others. The purpose of this review is to look into the studies on the emotional impacts of excessive internet use. Hence the objective of this paper is to highlight the consequences of excessive use of the internet. This review summarises the key findings and conclusions of previous work, and